MULTIDRUG RESISTANCE (MDR) OF V. Parahaemolyticus - -, Marlina (Jurnal Riset Kimia, 2009)
Vol. 2, No. 2 ABSTRACT A total of 97 V. parahaemolyticus isolate from Padang were examined for their resistance to 15 antibiotics. V. parahaemolyticus isolated behaved as resistant to sulfamethoxazole (100%), rifampin (95%) and tetracycline (75%) and sensitive to norfloxacin (96%). Ampicillin still sensitive for V. parahaemolyticus isolated from human stools. All of isolates were sensitive to namely chloramphenicol and floroquinolones (ciprofloxacin and norfloxacin agents). RAPD-PCR profiling with three primers (OPAR3, OPAR4 and OPAR8) produced four major clusters (R1, R2, R3 and R4), 7 minor clusters (I, II, III, IV, V, VI and VII) and three single isolates.  Keywords: V. parahaemolyticus, MDR, RAPD  1. D. Ottaviani, I. Bacchiocchi, L. Masini, F. Leoni, A. Carraturo, M. Giammarioli, and G. Sbaraglia, Antimicrobial susceptibility of potentially halophilic vibrios isolated from seafood, International Journal of Antimicrobial Agents 18: 135-140, (2001).2. A. Cespedes, and E. Larson, Knowledge, attitude and practices regarding antibiotic use among Latinos in the United States: Review and Recommendations, American Journal of Infection Control 34: 495-502, (2006).3. M. Lesmana, D. Subekti, C.H. Simanjuntak, P. Tjaniadi, J. R. Campbell, and B. A. Ofoyo, Vibrio parahaemolyticus associated with cholera-like diarrhea among patients in North Jakarta, Indonesia, Diagnostic Microbiology and Infectious Disease, 39: 71-75, (2001).4. S. Lu, B. Liu, B. Zhou, And R. E. Levin, Incidence and Enumeration of Vibrio parahaemolyticus in Shellfish from two retail Sources and the Genetic Diversity of isolates as Determined by RAPD-PCR Analysis, Food Biotechnology, 20: 193-209, (2006).5. M. Nishibuchi, Vibrio parahaemolyticus. In International handbook of foodborne pathogens, ed. M.D. Milliots and J. W. Bier, United States: Marcel Dekker, Inc. P, 2004, 237-252.6. L. Poirel, M. R. Martinez, H. Mammeri, A. Liard, and P. Nordmann, Origin of Plasmid-Mediated Quinolone Resistance Determinant QnrA, Antimicrobial Agents and Chemotherapy, 49: 3523-3525, (2005).7. S. Radu, N. Elhadi, Z. Hassan, G. Rusul, S. Lihan, N. Fifadara, Yuherman and E. Purwati, Characterization of Vibrio vulnificus isolated from cockles (Anadara granosa): antimicrobial resistance, plasmid profiles and random amplification            of polymorphic DNA analysis, FEMS Microbiology Letters, 165: 139–143, (1998).8. S. Radu, N. Ahmad, F. H. Ling, and A. Reezal, Prevalence and resistance             to antibiotics for Aeromonas species from retail fish in Malaysia, International of Journal Food Microbiology, 81: 261–266, (2003).9. B. Sarkar, N. R. Chowdhury, G. B. Nair, M. Nishibuchi, S. Yamasaki, Y. Takeda, S. K. Gupta, S. K. Bhattacharya, and Ramamurthy, Molecular characterization of Vibrio parahaemolyticus of similar serovars isolated from sewage and clinical cases of diarrhea in Calcutta, India,   World Journal of Microbiology and Biotechnology, 19: 771-776, (2003). 10. S. Schwarz, and E. Chaslus-Dancla, Use of antimicrobials in veterinary medicine and mechanisms of resistance, Veterinary Residue, 32: 201–225, (2001).11. H. Sörum, and T.M. L’Abèe-Lund,.  Antibiotic resistance in food-related bacteria – a result of interfering with the global web of bacterial genetics, International Journal of Food Microbiology, 78: 43–56, (2002).12. P. Tjaniadi, M. Lesmana, D. Subekti, N. Machpud, S. Komalarini, W. Santoso,     C. H. Simanjuntak, N. Punjabi, J. R. Campbell, W. K. Alexander, H. J. Beecham, A. L. Corwin, and B. A. Oyofo, Antimicrobial Resistance of Bacterial Pathogens Associated with Diarrheal Patients in Indonesia, American Journal   of Tropical Medicine and Hygiene,             68: 666-670, (2003).13. X. Zhao, and D. Drlica, Restricting              the Selection of Antibiotic-Resistant Mutants: A General Strategy Derived     from Fluoroquinolone Studies, Clinical Infectious Diseases, 33: S147-S156, (2001).